Environmental Impacts of Small Hydropower Plants - A Case Study of Borås Energi och Miljö’s Hydropower Plants - Sundqvist, Nathalie; Steinmetz, Maria (My University, 2014)
The use of hydropower in the society has a long history that started more than 2000 years ago. In Sweden, the first hydropower plants used for producing electricity were commissioned in the 1890s. The major expansion of hydroelectric power in Sweden took place in the 1940s- 1970s. Today there are about 2000 hydropower plants in Sweden, accounting for in average 45% of the electricity production. Of these 2000 hydropower plants a large majority are so called small-scale hydropower plants. The aim of this Master’s thesis is to do an environmental review of the four hydropower plants owned by Borås Energi och Miljö. The four hydropower plants, Haby, Hulta, Häggårda and Axelfors, were all built and commissioned in the first part of the 1900s in a time when the requirements on the companies to also take the environmental impacts into consideration were small. The four plants are small-scale hydropower plants and located in two tributaries to Viskan, Slottsån and Häggån and in Ätran. In order to gain knowledge about the environmen- tal impacts hydropower plants can result in, the project started with a literature study where scientific articles, reports and studies performed on hydropower plants were included. Also reports and previous studies performed about the four specific hydropower plants were looked at. The information from the literature study was used together with the information about the hydropower plants in the analysis to do an environmental review of the hydropower plants. The analysis showed on how complex the impacts from hydropower on the environment are and that there are both direct and indirect impacts on the species living in the areas around the hydropower plants. The main impacts proved to come from the migration barriers that the hydropower plants constitutes, the changes in the water flow due to the regulation of the plants and especially the short-term regulation in Haby and Hulta, and the dry riverbeds that the di-version of the water has caused. The literature study included also different measures that can be performed in order to mitigate or avoid the environmental impacts hydropower plants are resulting in. For the hydropower plants in this case, the focus should be on building fishways to that the species living in the stream can migrate as they could before the construction of the hydropower plants, start a min- imum flow in the original riverbeds so that once existing aquatic life can be restored and start to regulate the water flow so that follows a more natural patter. Borås Energi och Miljö should also perform biotope adjustments to improve spawning sites for the fish. The thing that mainly has hampered this environmental review was that information about the conditions at the sites before the construction were very limited due to the age of the plants. It has, however been possible to conclude that the four hydropower plants owned by Borås Energi och Miljö have effects on the environment. The impacts are possible to avoid or mitigate by different measures. The measures will result in costs but it is the only way to reduce the impacts the hydropower plants have today.
Keywords: Havs- och vattendragsteknik; Ocean and River Engineering